Investigation of chatter arising in Machine Tool-Fixture Work (MTFW) system during turning - Amin, A. K. M. Nurul; Khalil , Md. Khaled (1994)
Experimental investigations have been conducted to determine the influence of the rigidity of tool holder, cutting variables and tool geometry on machine tool chatter during turning of different grades of carbon steel with cemented carbide tools. Experimental results show that these variables maintain definite relationship with the frequency, amplitude and cutting speed range of high frequency chatter. A mathematical model has been developed to calculate the frequencies of the natural vibration of the tool holders. Finally it was concluded that high frequency chatter of machine tools during turning can be controlled by selecting the appropriate values of the rigidity of the tool holder, proper combination of cutting speed, feed and depth of cut and geometry bf the tool.